2012
DOI: 10.1063/1.3702453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular beam epitaxial growth and characterization of InSb1 − xNx on GaAs for long wavelength infrared applications

Abstract: Growth of InSb epilayers and quantum wells on Ge(001) substrates by molecular beam epitaxy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…These experimental studies, along with qualitative analysis using an analytical relation between effective vapor composition and NW chemical composition, not only enabled better understanding on the influence of different growth parameters on NW growth but also provided insight to a two-step growth temperature process with a corresponding Ga flux variation during growth. Although a two-step growth technique is not new for thin films 2427 and NW synthesis by chemical vapor deposition (CVD) technique 2628 , it is not common for NWs grown by MBE 29 . It has been reported that both binary and ternary III-V NWs synthesized by two-step CVD method exhibited long, straight, limited radial growth and excellent crystallinity when compared to NWs grown at invariant growth temperature via a single-step CVD growth technique 28, 30, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…These experimental studies, along with qualitative analysis using an analytical relation between effective vapor composition and NW chemical composition, not only enabled better understanding on the influence of different growth parameters on NW growth but also provided insight to a two-step growth temperature process with a corresponding Ga flux variation during growth. Although a two-step growth technique is not new for thin films 2427 and NW synthesis by chemical vapor deposition (CVD) technique 2628 , it is not common for NWs grown by MBE 29 . It has been reported that both binary and ternary III-V NWs synthesized by two-step CVD method exhibited long, straight, limited radial growth and excellent crystallinity when compared to NWs grown at invariant growth temperature via a single-step CVD growth technique 28, 30, 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Dilute nitride III–V semiconductor alloys in thin films with variable bandgap have been on the extensively studied material systems [ 1 – 10 ] for optical telecommunications applications. Introduction of very low nitrogen concentrations is sufficient to modulate the band gap of such systems over a wide range.…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of technologies for fabricating the RS layer, such as atomic layer deposition (ALD), [32] sputter, [33] pulsed layer deposition (PLD), [34] sol-gel process, [35] chemical solution deposition (CSD), [26][27][28]36] chemical vapor deposition (CVD), [37,38] e-beam evaporation deposition, [39] and molecular beam epitaxy (MBE). [40,41] Among a variety of fabricating methods, sputter, which can deposit well-controlled thin films, is most popular. CSD is a cost effective and highly flexible method that allows for good film quality at moderate annealing temperatures.…”
Section: The Memristor and Spiking Neural Network (Snn)mentioning
confidence: 99%